Bioactivity of Essential Oil from Atalantia buxifolia Leaves and its Major Sesquiterpenes against Three Stored-Product Insects. Issue 1 (2nd January 2020) - Pang, Xue; Almaz, Borjigidai; Qi, Xiao-Jie; Wang, Yang; Feng, Yi-Xi; Geng, Zhu-Feng; Xi, Chao; Du, Shu-Shan
Abstract: The insecticidal and repellent activities of the essential oil (EO) from Atalantia buxifolia leaves were evaluated against three stored product insects, including Tribolium castaneum, Lasioderma serricorne and Liposcelis bostrychophila . The EO obtained by hydrodistillation was investigated by GC-FID and GC-MS. Twenty-four compounds were identified and the principal components in the EO were β-caryophyllene (25.8 %), caryophyllene oxide (19.1 %) and epiglobulol (7.5 %). In this paper, the bioactivity of the obtained EO and its two major components were investigated by contact and repellent activity bioassay. The EO showed significant contact activity against T. castaneum, L. serricorne and L. bostrychophila adults with LD50 values of 23.9 μg/adult, 15.2 μg/adult and 54.6 μg/cm 2, respectively. And at the highest testing concentration ( T. castaneum and L. serricorne : 78.63 nL/cm 2 ; L. bostrychophila : 63.17 nL/cm 2 ), the repellent effect of the EO on three target insects was comparable to that of the positive control (DEET) after 2 h of exposure. For components, β-caryophyllene and caryophyllene oxide showed different levels of contact and repellent activities against three target insects. These results suggest that the EO from A. buxifolia leaves and its two major components have potential to be developed as natural insecticides and repellents for the control of stored product insect pests.